2015
DOI: 10.1002/jmri.25107
|View full text |Cite
|
Sign up to set email alerts
|

Interstudy repeatability of self‐gated quantitative myocardial perfusion MRI

Abstract: Purpose To evaluate the inter-study repeatability of multi-slice quantitative cardiovascular magnetic resonance myocardial blood flow (MBF), myocardial perfusion reserve (MPR), and extracellular volume (ECV). A unique saturation recovery self-gated acquisition was used for the perfusion scans. Materials and Methods An ungated golden angle radial turboFLASH pulse sequence was used to scan 10 subjects on two separate days on a 3T scanner. A single saturation pulse was followed by a set of 4 slices. Rest and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…[43][44][45][46][47] Direct comparison with the reproducibility of PET-based myocardial perfusion measurements is hampered by different measures of repeatability used in different studies and wide time ranges between the repeated measures in some studies. However, the repeatability coefficients reported in some MRI studies 44,47 are somewhat higher and the ICC somewhat lower 44,46 than in the previously mentioned PET-studies. 41,42 Morton et al 21 reported weak correlations for absolute perfusion values when comparing rest and stress perfusion values separately (r = 0.32 and r = 0.37, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46][47] Direct comparison with the reproducibility of PET-based myocardial perfusion measurements is hampered by different measures of repeatability used in different studies and wide time ranges between the repeated measures in some studies. However, the repeatability coefficients reported in some MRI studies 44,47 are somewhat higher and the ICC somewhat lower 44,46 than in the previously mentioned PET-studies. 41,42 Morton et al 21 reported weak correlations for absolute perfusion values when comparing rest and stress perfusion values separately (r = 0.32 and r = 0.37, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several MRI studies reported an underestimation of MBF . In those studies, the MBF values were analyzed with regard to issues of quantification algorithms, applied MRI signal intensity corrections, interstudy repeatability, or motion correction .…”
Section: Discussionmentioning
confidence: 99%
“…65 In fact, several MRI studies reported an underestimation of MBF. 3,[66][67][68][69][70][71][72][73] In those studies, the MBF values were analyzed with regard to issues of quantification algorithms, 69 applied MRI signal intensity corrections, 70 interstudy repeatability, 71 or motion correction. 72 For hyperemia, MBF underestimation was more pronounced in comparison to microsphere perfusion measurements 70,73 ; however, it is well-known that the microsphere technique somewhat overestimates MBF in regions of high flow, and underestimates MBF in regions of low flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECV has been validated as a marker of myocardial fibrosis and infarction. Studies have shown good accuracy and repeatability for ECV estimation using T1 mapping (20)(21)(22). Over these years, pharmacokinetic modelling of myocardial perfusion has also evolved.…”
Section: Theorymentioning
confidence: 99%